Development of sensory-based inclusive vocational modules in graphic design: a case study of neurodivergent learners in a vocational training institution - Nurfarina, Anne; Herdiana, Firli (Gelar: Jurnal Seni Budaya, 2025)
The purpose of this study is to develop a sensor-based vocational learning module that is appropriate for neurodivergent individuals, such as those with autism, as well as those who are enrolled in the LPK ATC Widyatama Program Desain Grafis. This module integrates sensor-based learning strategies and natural stimulation to increase students' understanding and engagement. Drawing from Ayres' theory of sensor integration, Vygotsky's theory of sociocultural education, and TPACK's work ethics, this module aims to improve cognitive, affective, and psychomotor learning. This study employs a qualitative case study methodology based on Design Thinking principles, which helps students understand the learning context. Interviews, artifact analysis, and observation are used to assess the learning process and results. The study's findings indicate that individualized sensory stimulation, such as visual references from movies, television shows, and video games, helps consumers develop ideas into products' graphic design. Among the things that are discussed are individual accommodations and the improvement of the instructional environment. This study offers a starting point for vocational education with recommendations for more comprehensive sensor integration.